A Nutritional Approach to the Use of Anticoccidial Vaccines in Broilers: Glutamine Utilization in Critical Stages of Immunity Acquisition - Mussini, F.J.; Goodgame, S.D.; Lu, C.; Fiscus, S.M.; Waldroup , P.W. (International Journal of Poultry Science, 2012)
The utilization of vaccines has proven to be a good strategy to prevent coccidiosis but the process of immunity acquisition needs to be approached from a nutritional point of view as well if complete success in broiler performance is to be achieved. It has been reported that Glutamine (GLU) plays a key role both in the gastrointestinal tract and the immune system and its utilization could be beneficial to cocci-vaccinated broilers. In this study, twelve hundred one-day-old male chicks were vaccinated at a commercial hatchery with a coccidiosis vaccine and randomly allocated to four treatments, each of which had six replications with 50 birds per pen. Birds were maintained in pens with built up wood shavings litter. Each treatment consisted of the same basal diet that met average nutrient levels in the U.S. poultry industry with four different inclusion rates of GLU (0, 0.5, 0.75 and 1%). Birds were fed the experimental diets from 1 to 28 days of age and a common unsupplemented diet to 42 d. Body weights were significantly improved at 21 and 28 days for all the treatments where the GLU was included. Feed conversion was not significantly affected by the inclusion of GLU. There were no significant differences in body weight and feed conversion at 42 days but the numerical difference in weight between the control and the treatments with GLU observed earlier were maintained. At 43 days, eight birds per pen were processed in a pilot processing plant. Breast meat yield was not significantly different among treatments. Glutamine proved to be beneficial during the process of immunity acquisition improving broiler performance significantly until 28 days and maintaining the body weight difference until the end of the experiment.